PENDAMPINGAN PENATAUSAHAAN DAN PENYUSUNAN LAPORAN KEUANGAN UMKM BERBASIS DIGITAL DI KAMPUNG ENGGROS - Ulfah Rizky Muslimin; Elia Madatu Tandililing; Putri Ratnasari; Maria Apriyane Patty; Rizka Aisyah Nurjannah; Bucek Jalu Prasetyo Arjuna; Gian Giovania; Yulianti Karoma; Alfonsina S.S Wanma (LPPM Institut Pendidikan Nusantara Global, 2026)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in supporting national and regional economic stability. In Papua, the MSME sector continues to develop as a key driver of the local economy. However, many MSME actors still face challenges in financial management, such as the lack of transaction recording, the absence of separation between personal and business finances, and limited understanding of financial reporting. This condition results in a low ability to control cash flow and to access formal financing sources. The use of digital technology through financial applications has become an effective solution to improve efficiency and transparency in MSME financial management. One recommended application is SIAPIK (Sistem Informasi Aplikasi Pencatatan Informasi Keuangan), developed by Bank Indonesia, which helps business actors prepare simple digital-based financial reports. This community service activity was conducted in Kampung Enggros, Distrik Abepura, Kota Jayapura, Provinsi Papua, aiming to provide assistance in bookkeeping and the preparation of digital-based financial reports for local micro business actors. The methods used include socialization, training, and participatory assistance in the use of the SIAPIK application. The results show a significant improvement in participants’ understanding of transaction recording, asset management, pricing determination, and receivables and payables management. In addition, business actors are able to operate the SIAPIK application independently and produce valid financial reports to support decision-making and access to financing.